A CROSS-SECTIONAL STUDY ON EVALUATION OF DIAGNOSTIC APPLICATIONS OF LINEAR SONOGRAPHIC TRANSDUCER IN VARIOUS DISEASES - Chauhan, Tarun; Kumar, Vaibhav; Rai, Ritika (International Journal For Research In Health Sciences And Nursing, 2022)
Introduction: An ultrasonography scan is a medical test that uses high-frequency sound waves to produce live images of the body. Linear transducer is used to create the images of superficial organs. Superficial sonography used for diagnose various pathologies like Large vessel vasculitis, carpel tunnel syndrome, thyroiditis, carotid artery disease etc. The aim of this study is to evaluate the diagnostic application of linear sonographic transducer in various diseases of superficial organs. In the simple sense of word, Transducers are the devices that converts a form of energy into another. These devices have been throughout the history, taking an example of Pythagoras in 550 BC, who sited that pitch and frequency is co-related and this lead to creation of Sonometer, instrument used in music1. A major physics breakthrough occurred in 1880 when the brothers Jacque and Pierre Curie demonstrated the piezoelectric effect, which results in formation of Ultrasound transducer. Over 60 years later, Dr Karl Dussik of Austria in 1940s, becomes the first physician to use the ultrasound in medical diagnosis2. Research Methodology: In this prospective cross-sectional study 40 patients, prescribed for superficial organs ultrasonography (USG) (thyroid neck, musculoskeletal, and doppler) were included and stat for result was mean and percentage stats used. This was a quantitative prospective cross sectional study in which high frequency ultrasonography of a maximum of 40 patients with proper indication under taken. Ultrasonography is performed after taking proper history and relevant physical examination performed by the linear transducer (6 – 12 MHz). In this study convenience sampling was used as the sample was taken from a section of the population that was easily accessible or readily available to the researcher. Findings: Total 40 (100%) patient’s data used in this study who undergone the superficial organ examination (Musculoskeletal, Doppler, thyroid neck) during the period of study. Out of which 50% (20) patients undergo Thyroid ultrasonography, 25% (10) patients undergo musculoskeletal ultrasonography and 25% (10) patients undergo Doppler imaging ultrasonography. Result of scan collected and master chart is prepared. Author found that in thyroid ultrasonography scan 15% patients have swollen neck and pain was due to cervical varicocele, 12.5% patients have lymph nodes, 2.5% patients have goitre, 2.5% patients have thyroiditis, 2.5% patients have cyst, 2.5 % patients have thyroid mass, and 12.5% patients have normal study. In Doppler ultrasonography scans 5% patients have edema, 2.5% patients have varicocele, 5% patients have varicosities, 2.5% patients have periphery arterial disease and 5% patients have thrombus/plaque and 5% have normal scan with no findings. In musculoskeletal ultrasonography scans 22.5% patients have normal study with no significant findings and 2.5% patients have focal encepahalocele. Conclusion: It is concluded that ultrasound is the best modality to rule out the problems at any stage so that treatment can be started on behalf of reports of Ultrasonography scan in patients of superficial organs with various diseases, as it is fast and safe to patients, it does not include any ionizing radiation so female patients of reproductive age go through scan without any risk. And most common reason of swelling and pain in neck is cervical lymphadenopathy, lymph nodes, mass or goitre, and pain in joints and swelling is varicosities or thrombus in lower extremities and in musculoskeletal cranium study mostly has normal study with no significance but few have focal encepahalocele as per in this study.